The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-67800-1
|View full text |Cite|
|
Sign up to set email alerts
|

Ophidiomycosis surveillance of snakes in Georgia, USA reveals new host species and taxonomic associations with disease

Abstract: Ophidiomycosis (snake fungal disease) is caused by the fungus Ophidiomyces ophiodiicola and threatens snake health worldwide. It has been documented throughout the eastern United States and severe cases have recently been reported in Georgia, USA. To evaluate disease distribution and prevalence in this state, 786 free-ranging snakes were examined for skin lesions consistent with ophidiomycosis and swabbed to detect O. ophiodiicola DNA using qPCR. Sampled snakes represented 34 species and 4 families; 27.5% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 48 publications
5
20
0
Order By: Relevance
“…Consistent with our observations, other studies have shown that Oo prevalence differs intra-generically among Nerodia 44 . In our study, N. h. harteri exhibited higher Oo prevalence compared to N. rhombifer , which is concerning owing to the conservation status and rarity of N. h. harteri .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our observations, other studies have shown that Oo prevalence differs intra-generically among Nerodia 44 . In our study, N. h. harteri exhibited higher Oo prevalence compared to N. rhombifer , which is concerning owing to the conservation status and rarity of N. h. harteri .…”
Section: Discussionsupporting
confidence: 93%
“…Factors that contribute to the probability of Oo infection and mortality among individuals and species vary considerably, although some studies have shown climate and season are associated with incidence and severity of infection 12,17,18,[41][42][43] . However, interspecific 44 and demographic factors 18 associated with pathogen prevalence are still understudied. One study presented evidence of interspecific Oo prevalence differences in Georgia (USA) 44 , and another documented vertical transmission of Oo from infected mothers to neonates among viviparous and oviparous snakes 45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snake infections by O. ophiodiicola have been reported in the US, Canada, the UK, Germany, the Czech Republic and Australia (Franklinos et al., 2017; Lorch et al., 2016), and this snake fungal disease (SFD) has been found in more than 30 species of wild and captive individuals belonging to six different families (Haynes et al., 2020; Lorch et al., 2016). The red‐banded snake and Chinese cobra are mainly distributed in Asian countries and are native to Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization between lineages is also expected to occur more frequently in regions with high Oo prevalence (i.e., more opportunities for co-infections). Thus far, in-depth studies of Oo prevalence in snake communities have been very limited in their geographic scope (e.g., [20,38,39]). Future work would be beneficial to understand the relationship between prevalence and the abundance of hybrid strains.…”
Section: Discussionmentioning
confidence: 99%